Stability Analysis and Transient Attraction Dynamics of Flat-Top Solitons via Modulated Driving Fields in Normal Dispersion Microcavity - Xueying Jin; Xin Xu; Yang Lu; Haoran Gao; Liandong Yu (IEEE Photonics Journal, 2020)
We theoretically and numerically investigate the stability and transient attraction dynamics of flat-top solitons (or platicons) in normal group velocity dispersion (GVD) microcavity via modulation-assisted four wave mixing instead of mode interaction. The spatial bifurcation structure of the stationary states depending on modulation power, pump power and cavity detuning is mapped, indicating a significantly extended existence range by the modulation-assisted approach. We explore the transformation between discrete energy spectrum of dark solitons and a quasi-continuous spectrum of platicons with and without a third-order dispersion and identify the connections between these two states. Robust trapping and manipulation of temporal platicons is also verified by implementation of phase modulation, and explained by transient attraction dynamics. One may manipulate the duration of the pulse by varying modulation power, pump power, or cavity detuning. Specifically, the effect of high-order dispersion on Kerr frequency comb generation is studied, and the results show that different orders of GVD term affect the 3dB comb bandwidth, repetition rate, spectral position of dispersive waves, as well as temporal profile and pulse peak power.